KONFLIK SOSIAL PEREBUTAN LAHAN PERKEBUNAN - Ramadani, Frizky Eka (Paradigma, 2022)
Humans have the will to rule over their interests with other people. Conflicts that are eliminated from the existence of interests are like the agrarian conflicts that exist in Banyuwangi Regency, between the Rukun Tani of Sumberejo Pakel Village and company. The purpose of this research is to analyze the background of the causes of conflict, forms of conflict, conflict conflicts, and conflict resolutions that occur. The approach used is qualitative, the theory of conflict of interest perspective of Ralf Dahrendorf. The results of the research show that the cause of the conflict is the difference in the real and hidden interests of the subordinate and superordinate groups. The existence of an unbalanced position, shows the forms of conflict in this matter include, horizontal conflict, vertical conflict, conflict, and realistic conflict leading to an open agreement, demands for trials of acts of violence and human rights justice , and demands for disclosure of public information on Hak Guna Usaha (HGU) owned business. This century of conflict has had both positive and negative impacts as a form of change affected by the conflict. There is an aspiration to immediately end the conflict with settlement efforts that have been made including coercion, conciliation, mediation, and adjudication. Sociological analysis from the perspective of Ralf Dahrendorf’s theory states that, society is a subordinate group that does not have authority in determining policies, so they do not have full authority over the demands made on superordinates. Keywords: Agrarian; Conflict; Community; Plantation; Social